Intrinsically Biocompatible Polymer Systems (2020)
Biocompatibility refers to the ability of a biomaterial to perform its desired function with respect to a medical therapy, without eliciting any undesirable local or systemic effects in the recipient or beneficiary of that therapy, but generating the most appropriate beneficial cellular or tissue response in that specific situation, and optimizing the clinically relevant performance of that therapy, which reflects current developments in the area of intrinsically biocompatible polymer systems. Polymeric biomaterials are presently used as, for example, long-term implantable medical devices, degradable implantable systems, transient invasive intravascular devices, and, recently, as tissue engineering scaffolds. This Special Issue welcomes full papers and short communications highlighting the aspects of the current trends in the area of intrinsically biocompatible polymer systems.